Exploring entrepreneurial characteristics among university students: an evidence from India. Issue 3 (2nd October 2019) - Anwar, Imran; Saleem, Imran
Abstract : Purpose: The purpose of this paper is to explore the entrepreneurial characteristics among university students in India studying business and also comparing the levels of entrepreneurial characteristics between entrepreneurially inclined and entrepreneurially not inclined students. Design/methodology/approach: In this study, the authors included six entrepreneurial characteristics, namely, risk taking propensity, innovativeness, locus of control, need for achievement, general self-efficacy and tolerance for ambiguity to define the entrepreneurial profile of students. Convenient sampling was used for collecting the data using a seven-point Likert scale based on 38-items self-administered questionnaire. Data were collected from three universities of different cities, namely, Aligarh Muslim University, Aligarh, CSJM University, Kanpur and KMCUAF University, Lucknow. In total, 300 questionnaires were distributed in each of the universities, and 719 questionnaires were found statistically suitable for the study. Students were asked the question "What career option are you planning to choose after completing your graduation?" to know the inclination of the students. Findings: Results of the t -test confirmed that levels of all the entrepreneurial characteristics are higher in entrepreneurially inclined students when compared to entrepreneurially not inclined students except in terms of general self-efficacy. Thus, entrepreneurially inclined students carry higher risk taking propensity, innovativeness, locus of control, need for achievement and tolerance for ambiguity. Research limitations/implications: This study is confined only to undergraduate students from business background, and only three universities were included in the sample. Further research can be done taking students from different streams, namely, engineering, science and technology and arts etc. University-wise studies can also be conducted with the view to bring comparability among the students in terms of levels of entrepreneurial characteristics based upon the inclination shown. Practical implications: This research provides the deeper understanding about what course contents are effective in developing entrepreneurial characteristics among the students and what are to be added with the view to raise potential entrepreneurs. Originality/value: This paper contributes to establishing the differences across different entrepreneurial characteristics between entrepreneurially inclined and non-inclined undergraduate students.